Lyophilized Human Bone Allograft as an Antibiotic Carrier: An In Vitro and In Vivo Study - Débora C. Coraça-Huber; Stephan J. M. Steixner; Stevo Najman; Sanja Stojanovic; Ronja Finze; Denis Rimashevskiy; Dina Saginova; Mike Barbeck; Reinhard Schnettler (MDPI AG, 2022)
Background: Antibiotics delivered from implanted bone substitute materials (BSM) can potentially be used to prevent acute infections and biofilm formation, providing high concentrations of antibiotics at the surgical site without systemic toxicity. In addition, BSM should allow osteoconductivity supporting bone healing without further surgery. Promising results have been achieved using lyophilized bone allografts mixed with antibiotics. Methods: In this study specially prepared human bone allografts were evaluated as an antibiotic carrier in vitro and in vivo. The efficacy of different antibiotic-impregnated bone allografts was measured by drug release tests in vitro and in vivo and bacterial susceptibility tests using four bacterial species usually responsible for implant-associated infections. Results: The loading procedures of allograft bone substitutes with antibiotics were successful. Some of the antibiotic concentrations exceeded the MIC90 for up to 7 days in vitro and for up to 72 h in vivo. The susceptibility tests showed that S. epidermidis ATCC 12228 was the most susceptible bacterial species in comparison to the other strains tested for all antibiotic substances. Vancomycin and rifampicin showed the best results against standard and patient-isolated strains in vitro. In vivo, new bone formation was comparable in all study groups including the control group without antibiotic loading. Conclusions: Human bone allografts showed the capacity to act as customized loaded antibiotic carriers to prevent acute infections and should be considered in the management of bone infections in combination with systemic antimicrobial therapy.